Minimal residual disease monitoring: the new standard for treatment evaluation of haematological malignancies? (Swiss Medical Weekly, 2014)
Minimal residual disease (MRD) refers to the small number of malignant cells that remain after therapy when the patient is in remission and shows no symptoms or overt signs of disease. Current treatment protocols for haematological malignancies allow most patients to obtain some form of MRD state, but cure seldom follows and in most cases fatal relapses occur sooner or later, leaving a bitter impression of having won a battle yet lost the war. MRD detection and quantification are used for evaluation of treatment efficiency, patient risk stratification and long-term outcome prediction. Whereas multicolour flow cytometry (MCFC) and polymerase chain reaction (PCR) based methods constitute the two most commonly used techniques for MRD detection, next generation sequencing will certainly be widely employed in the future. As MRD reflects the nature of the malignant disease itself, including its sensitivity to the drug regimens applied, it constitutes the ideal method for surveillance and patient follow-up. The morphological examination of peripheral blood or bone marrow smears, although still an indispensable part of routine laboratory testing, is clearly insufficient for patient management, and clinicians should not ask themselves whether to look for MRD or not, but how and when.